Inhibition of Carotenoid Synthesis as a Mechanism of Action of Amitrole, Dichlormate, and Pyriclor - Burns, Earl R. (1971)
Amitrole (3-amino-s-triazole), dichlormate (3,4-dichlorobenzyl methylcarbamate), and pyriclor (2,3,5-trichloro-4-pyridinol) inhibited normal carotenogenesis in etiolated wheat (Triticum aestivum L. var. Coker 65-20) seedlings. Carotenoid precursors accumulated in treated plants. In dichlormate-treated plants, ζ-carotene accumulated, whereas phytofluene, phytoene, and ζ-carotene accumulated in amitrole- and pyriclor-treated plants. None of the herbicides interfered with protochlorophyllide synthesis or its conversion to chlorophyllide when etiolated plants were illuminated. Chlorophyll accumulated in treated plants exposed to light at 60 foot candles, but was unstable and partially destroyed by illumination at 4000 foot candles. These data suggest that the phytotoxicity of amitrole, pyriclor, and dichlormate is due to inhibition of the synthesis of carotenoids and to the consequent photodestruction of chlorophyll and chloroplast disruption.